Ice in the Tropics: the Export of ‘Crystal Blocks of Yankee Coldness’ to India and Brazil - Herold, Marc W. (Revista Espaço Acadêmico, 2011)
The Boston natural ice trade thrived during 1830-70 based upon Frederic Tudor’s idea of combining two useless products – natural winter ice in New England ponds and sawdust from Maine’s lumber mills. Tudor ice was exported extensively to the tropics from the West Indies to Brazil and the East Indies as well as to southern ports of the United States. In tropical ice ports, imported natural ice was a luxury product, e.g., serving to chill claret wines (Calcutta), champagne (Havana and Manaus), and mint juleps (New Orleans and Savannah) and used in luxury hotels or at banquets. In the temperate United States, natural ice was employed to preserve foods (cold storage) and to cool water (Americans’ peculiar love of ice water). In both temperate and tropical regions natural ice found some use for medicinal purposes (to calm fevers). With the invention of a new technology to manufacture artificial ice as part of the Industrial Revolution, the natural ice export trade dwindled as import substituting industrialization proceeded in the tropics. By the turn of the twentieth century, ice factories had been established in half a dozen Brazilian port cities. All that remained of the once extensive global trade in natural ice was a sailing ship which docked in Rio Janeiro at Christmas time laden with ice and apples from New England.